Exploring the Role of Kurdish (Sorani Dialect) as a L1 in Teaching English as a Second Language: A Case Study of Erbil City Schools - Rozhvin Adnan Rasheed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The current study aims at investigating teachers’ perception on the use of L1 (Kurdish) specifically Sorani dialect in teaching English as a second language. It was hypothesized that teachers' use of the first language (L1) in teaching the second language (L2) positively impacts students' English proficiency and enhances the overall effectiveness of the teaching and learning process. The data was collected from 60 English language teachers at several schools in Erbil city using a quantitative research method, SPSS package for analyzing the data. The results demonstrate that teachers have a positive perception of using L1 in teaching L2. These findings suggest that the strategic use of L1 can enhance several aspects of the learning process: it facilitates comprehension of complex concepts, reduces learner anxiety by creating a more comfortable classroom environment, and supports vocabulary acquisition through translation and context. The justification for these results lies in the empirical data collected, which reflect teachers' practical experiences and observations. Teachers reported that using L1 helps bridge linguistic gaps, making it easier for students to grasp new concepts and retain vocabulary, thereby leading to improved English proficiency. This study contributes valuable evidence to the discourse on language teaching methodologies, helping teachers understand when and to what extent they should use the first language in teaching L2 to enhance teaching effectiveness and learning outcomes.